Synchronization and leadership in string quartet performance: a case study of auditory and visual cues - Timmers, Renee; Endo, Satoshi; Bradbury, Adrian; Wing, Alan M. (Frontiers in Psychology, 2014)
Temporal coordination between members of a string quartet was investigated across repeated performances of an excerpt of Haydn’s string quartet in G Major, Op. 77 No. 1. Cross-correlations between interbeat intervals of performances at different lags showed a unidirectional dependence of Viola on Violin I, and of Violin I on Cello. Bidirectional dependence was observed for the relationships between Violin II and Cello and Violin II and Viola. Own-reported dependencies after the performances reflected these measured dependencies more closely than dependencies of players reported by the other players, which instead showed more typical leader-follower patterns in which Violin I leads. On the other hand, primary leadership from Violin I was observed in an analysis of the bow speed characteristics preceding the first tone onset. The anticipatory movement of Violin I set the tempo of the excerpt. Taken together the results show a more complex and differentiated pattern of dependencies than expected from a traditional role division of leadership suggesting several avenues for further research.